Răspuns:
Explicație pas cu pas:
a) 2 si 4
2 = 2
4 = 2^2
cmmdc = 2
cmmmc = 2^2 = 4
b) 3, 6 si 9
3 = 3
6 = 2*3
9 = 3^2
cmmdc = 3
cmmmc = 2*3^2 = 18
c) 10, 25 si 15
10 = 2*5
25 = 5^2
15 = 3*5
cmmdc = 5
cmmmc = 2*3*5^2 = 150
d) 8, 4 si 6
8 = 2^3
4 = 2^2
6 = 2*3
cmmdc = 2
cmmmc = 2^3*3 = 24
e) 12 si 15
12 = 2^2*3
15 = 3*5
cmmdc = 3
cmmmc = 2^2*3*5 = 60
f) 20, 30 si 60
20 = 2^2*5
30 = 2*3*5
60 = 2^2*3*5
cmmdc = 2*5 = 10
cmmmc = 2^2*3*5 = 60
g) 3, 12 si 18
3 = 3
12 = 2^2*3
18 = 2*3^2
cmmdc = 3
cmmmc = 2^2*3^2 = 36